A guide to agile communication - Defra digital - Digital, DEFRA (Departmetn for Environment, Food & Rural Affairs (UK), 2018)
This guide is intended for: people planning communications activity on behalf of agile teams people doing the communications activity (espec ially blogging, presenting, or filmmaking) people who manage the peopl e described above, who want to understand what they're doing and why T he government service standard encourages teams to work in the open as much as possible, echoing item 10 in the government design principles , “make things open, it makes them better”. This guide was written to help teams do just that.